2016
DOI: 10.2319/101515-693.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid maxillary expansion versus middle ear tube placement: Comparison of hearing improvements in children with resistance otitis media with effusion

Abstract: Objective:  To test the null hypothesis that there are significant differences in hearing improvements of children with resistance otitis media with effusion (OME) who undergo a rapid maxillary expansion (RME) procedure or ventilation tube placement. Methods:  Forty-two children between 4.5 and 15 years old were divided into three groups: RME, ventilation tube, and control groups. The RME group consisted of 15 children with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Should the prespecified endpoints be met, clinical implications of RME are manifold: (1) enhancing nasal breathing[ 18 19 20 ] and thus avoiding vital problems such as obstructive sleep apnea;[ 21 22 23 24 25 ] (2) preventing temporomandibular disorders; (3) avoiding the occurrence of skeletal and dental malocclusions that may require, at adulthood, an invasive orthognathic surgery;[ 26 ] and (4) facilitating hearing by relieving constriction at the level of the Eustachian tube. [ 27 ] Hence, there is a justification to conduct clinical studies to document the enhancement of nasal breathing and hearing by opening the Eustachian tube after RME.…”
Section: Discussionmentioning
confidence: 99%
“…Should the prespecified endpoints be met, clinical implications of RME are manifold: (1) enhancing nasal breathing[ 18 19 20 ] and thus avoiding vital problems such as obstructive sleep apnea;[ 21 22 23 24 25 ] (2) preventing temporomandibular disorders; (3) avoiding the occurrence of skeletal and dental malocclusions that may require, at adulthood, an invasive orthognathic surgery;[ 26 ] and (4) facilitating hearing by relieving constriction at the level of the Eustachian tube. [ 27 ] Hence, there is a justification to conduct clinical studies to document the enhancement of nasal breathing and hearing by opening the Eustachian tube after RME.…”
Section: Discussionmentioning
confidence: 99%
“…Kilic et al [ 9 ] compared the effects of RME and of a trans-tympanic tube placement on pure-tone threshold in children with recurrent otitis media with effusion (OME). They divided children into three groups: a control group, a ventilation tube placement group (children with resistant OME lasting at least 3 months and conductive hearing loss—CHL) and an RME group.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies (Cozza [ 12 ], Pirelli [ 13 ]) included children without evidence of an adenoidal blockage at the nasopharyngoscopic evaluation, eventually because of previous adenoidectomy or adenotonsillectomy (i.e., 73.8% of children included by Pirelli). Kilic [ 9 ] excluded children previously treated by adenotonsillectomy, but did not include information on adenoid dimension, such as Villano [ 8 ]. Conversely, De Stefano described, according to Cassano’s classification, the reduction in adenoidal tissue due to RME application.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review of 2017 on RME effects on auditory improvement also confirmed the thesis in seven studies over nine analyzed [21]: improvement in CHL was observed at the end of the retention period and was shown to be stable during a significant follow-up. Evaluation of the stability of CHL improvement was described during follow-up ranging from 10 to 12 months [19][20][21][22][23][24][25]. It has to be noted, though, that studies with 2-year follow-up employed a transpalatal arch for retention after removal of the maxillary appliance [23][24][25].…”
Section: Discussionmentioning
confidence: 99%